Time and Cost Estimation of Watu Sewu Bridge Construction on the South Cross Road LOT 7 Project Blitar - Saputri, Laili Dian; Prajitno, Achmad Faiz Hadi (Jurnal Transportasi: Sistem, Material, dan Infrastruktur, 2023)
The Southern Cross Road project is a project that aims to facilitate transportation in the south of East Java. One of the segments on the Southern Crossing Road is the LOT 7 project that connects the Tulungagung Regency boundary – Serang – Malang Regency boundary. This study discussed the construction of the Watu Sewu Bridge, which is one of the works in the Southern Cross Road project. This bridge used a concrete main structure and a steel frame. During the construction process, there were several obstacles, such as unfavorable weather and difficult field conditions that resulted in project delays. Time planning and selecting the proper implementation method can assist in managing resources effectively and efficiently. This study planned construction management for the Watu Sewu Bridge construction, which consists of the substructure, superstructure, and pavement structure work. This study was prepared by identifying work items and calculating volume and productivity. These calculations were used to determine the duration and cost of implementation. Project scheduling used the critical path method using the Microsoft Project program. Based on the analysis results, it was obtained the final results of the duration and time of implementation, network planning, and S curve. It is known that the implementation time for the construction of the Watu Sewu Bridge was 154 calendar days, and the implementation cost was IDR 22.312.359.417.